Soluble microneedle and ligustrazine transdermal patch
By combining soluble microneedles with transdermal patches, the problem of low bioavailability of tetramethylpyrazine preparations has been solved, achieving efficient and long-lasting transdermal drug delivery and significantly improving the clinical application potential of tetramethylpyrazine.
Patent Information
- Application Number
- CN202511225064.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-11-18
AI Technical Summary
Existing tetramethylpyrazine preparations, such as oral and injectable formulations, suffer from significant first-pass effect, short biological half-life, low bioavailability, and poor patient compliance, which limit their clinical application.
The method employs soluble microneedles combined with transdermal patches. Soluble microneedles are prepared using gelatin and hydroxypropyl methylcellulose, and a drug layer is prepared using polyacrylic acid resin, triethyl citrate, and isopropyl myristate to achieve physical and chemical penetration enhancement and improve transdermal drug delivery.
It significantly improved the bioavailability and medication compliance of ligustrazine, increased the cumulative penetration rate by 2.71 times in 24 hours, and maintained a stable release for 6 hours after reaching peak plasma concentration at 4 hours, eliminating the prolongation of half-life and reducing the first-pass effect in the liver.
Smart Images

Figure CN120960126A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of surgical supplies technology, and in particular relates to a soluble microneedle and a ligustrazine transdermal patch. Background Technology
[0002] Ligusticum chuanxiong is a very common blood-activating and stasis-removing herb in traditional Chinese medicine. It is warm in nature and pungent in taste, and enters the liver, gallbladder, and pericardium meridians. It has significant effects in activating blood circulation, regulating qi, dispelling wind, and relieving pain. As early as the *Shennong Bencao Jing* (Shennong's Classic of Materia Medica), it was recorded that Ligusticum chuanxiong "treats stroke with headache, cold-induced numbness, and muscle spasms." Tetramethylpyrazine (TMP), an amide alkaloid, is a bioactive monomer isolated from the rhizome of Ligusticum chuanxiong. Since the 1980s, TMP has been mainly used clinically for the treatment of cardiovascular and cerebrovascular diseases. Currently, the main dosage forms of TMP used clinically are oral and injectable formulations. However, oral TMP formulations have a significant first-pass effect, short biological half-life, and low bioavailability, while injectable formulations have poor patient compliance, greatly limiting the clinical application of TMP. Therefore, developing novel TMP formulations is of great significance. Summary of the Invention
[0003] In view of this, this invention focuses on developing a transdermal drug delivery formulation of tetramethylpyrazine. It innovatively employs soluble microneedles as a physical permeation enhancer, successfully preparing a soluble microneedle-tetramethylpyrazine transdermal patch. The aim is to establish and optimize its formulation and conduct quality evaluation, clarifying its pharmacokinetic parameters in rats. Through this research, we hope to improve patient compliance and enhance drug bioavailability, providing a safer, more effective, and convenient route of administration for the clinical application of tetramethylpyrazine.
[0004] The present invention provides a soluble microneedle, wherein the raw materials of the soluble microneedle include gelatin and hydroxypropyl methylcellulose.
[0005] In this invention, the mass ratio of gelatin to hydroxypropyl methylcellulose is 1:2; in actual operation of this invention, the height of the soluble microneedle is 760±20μm, the bottom diameter is 330±30μm, and the tip diameter is 18±2μm.
[0006] This invention also provides a method for preparing soluble microneedles, the method comprising the following steps:
[0007] (1) Preparation of matrix solution: Dissolve gelatin and hydroxypropyl methylcellulose in water at a mass ratio of 1:2 to prepare a matrix solution with a concentration of 15% w / w;
[0008] (2) Filling the mold: Place the matrix solution in the mold and centrifuge at 3000 r / min for 10 min;
[0009] (3) Drying and molding: The mold containing the matrix solution is dried at 50°C for 6 hours, and the soluble microneedles are obtained by demolding.
[0010] In this invention, in step (1), the dissolution temperature of gelatin is 90°C and the dissolution temperature of hydroxypropyl methylcellulose is 50°C.
[0011] The present invention also provides the application of the soluble microneedles described in any of the above claims in the preparation of transdermal drug delivery formulations.
[0012] This invention provides a ligustrazine transdermal patch, the transdermal patch comprising: soluble microneedles and a drug layer as described in any one of the above claims;
[0013] The drug layer contains the following components:
[0014] Polyacrylic acid resin IV, triethyl citrate, isopropyl myristate, and tetramethylpyrazine.
[0015] In this invention, the dosage of tetramethylpyrazine is 7.96% of the total mass of the transdermal patch layer;
[0016] The amount of polypropylene resin IV used is 48.90% of the total mass of the transdermal patch layer;
[0017] The amount of triethyl citrate used is 37.07% of the total mass of the transdermal patch layer.
[0018] The amount of isopropyl myristate used is 6.07% of the total mass of the transdermal patch layer.
[0019] The transdermal patch provided by this invention has the characteristic of highly efficient penetration enhancement. The transdermal patch combines soluble microneedles and isopropyl myristate, resulting in a cumulative penetration amount of 2877.384±159.28 μg / cm³ over 24 hours. 2 The transdermal efficiency was 2.71 times that of the blank patch. It also exhibits long-lasting sustained release; pharmacokinetic studies in rats showed that the blood drug concentration reached its peak at 4 hours after transdermal administration and maintained a stable release for 6 hours, with significantly lower fluctuations than intravenous injection. Furthermore, it boasts advantages such as high bioavailability and convenient and safe use. Attached Figure Description
[0020] Figure 1 A schematic diagram illustrating the preparation of a soluble microneedle-ligustrazine transdermal patch;
[0021] Figure 2 Morphology diagram of DMNs with a single matrix material (%, W / W);
[0022] Figure 3 Morphology diagram of DMNs composite matrix material (W / W);
[0023] Figure 4Morphology of DMNs prepared at different centrifugation speeds;
[0024] Figure 5 Morphology of DMNs prepared for different centrifugation times;
[0025] Figure 6 Morphology of DMNs prepared at different drying temperatures;
[0026] Figure 7 Morphology of DMNs prepared for different drying times;
[0027] Figure 8 This is a plot of the normal distribution of the residuals.
[0028] Figure 9 Contour plot and 3D plot showing the effects of the interaction between A and B on TMP Q24 h;
[0029] Figure 10 Contour plot and 3D plot showing the effects of the interaction between A and C on TMP Q24 h;
[0030] Figure 11 Contour plot and 3D plot showing the effects of the interaction between B and C on TMP Q24 h;
[0031] Figure 12 Comparison of cumulative release of transdermal patches using different penetration enhancement methods (n=3, x±SD)
[0032] Figure 13 The graph shows the changes in blood concentration of TMP in rats (n = 6, x ± SD). Detailed Implementation
[0033] For reagents or instruments used in the following text where specific technical or conditional specifications are not given, standard experimental conditions shall apply. If no reagent company instructions are explicitly provided, the conditions recommended in those instructions shall be followed. Reagents or instruments whose manufacturers are not specified are all commercially available standard products.
[0034] Example
[0035] 1. Screening of soluble microneedle single matrix materials
[0036] (1) In the experiment, PVP K29-32, PVP K88-96, PVA, GEL, HPMC, and AP were prepared into concentrations respectively.
[0037] The matrix solutions were prepared at concentrations of 10%, 15%, and 20%. Microneedles were fabricated, and their formability, demolding properties, needle formation rate, and aluminum foil puncture resistance were evaluated to determine the toughness and brittleness of the matrix material and to determine the optimal concentration of the matrix solution.
[0038] Table 1. Single matrix material formulations for DMNs (%, W / W)
[0039]
[0040]
[0041] (2) Screening results of soluble microneedle single matrix materials
[0042] The experiments investigated the brittleness and toughness of single matrix materials (PVP K29-32, PVP K88-96, PVA, HPMC, and GEL) and the effects of their concentrations (10%, 15%, and 20%) on DMNs. The experimental results are shown in Table 2 and [Table data missing]. Figure 2 .
[0043] Table 2 Screening of Single Matrix Materials for DMNs (%, W / W)
[0044]
[0045] From Table 2 and Figure 2 It is known that DMNs prepared using PVP K29-32, PVP K88-96, AP, and GEL as single matrix materials are prone to backing layer fracture during demolding due to their high brittleness. Although they can successfully pierce aluminum foil, needle breakage is common, classifying them as brittle materials. PVP K88-96 is particularly hygroscopic, requiring careful attention to storage conditions when using it to prepare microneedles. In aluminum foil puncture experiments, microneedles made of PVA and HPMC failed to penetrate the foil, and the needle tips exhibited bending. When the backing layer was bent, only deformation occurred without breakage. Compared to the other four materials, PVA and HPMC are both considered tough materials. When the concentration of the six matrix materials (PVP K29-32, PVP K88-96, PVA, HPMC, AP, and GEL) is 15%, the matrix solutions can all be successfully inserted into the mold and the microneedles can be guaranteed to have good formability. Therefore, the optimal concentration of the matrix solution for preparing DMNs is determined to be 15%. It is expected that the composite preparation of DMNs by combining brittle and tough materials can make up for the defects of DMNs with single matrix materials, so that DMNs have both the hardness to be successfully inserted into aluminum foil and the toughness to be not easily broken.
[0046] 2. Screening of soluble microneedle composite matrix materials
[0047] (1) Based on the evaluation results of the brittleness and toughness of single matrix material DMNs, composite DMNs were prepared according to the ratio in Table 3, and a comprehensive score was given according to the scoring criteria in Table 4.
[0048] Table 3. DMNs Composite Matrix Material Formulation (%, W / W)
[0049]
[0050] Table 4. Evaluation Criteria for DMNs Composite Matrix Materials
[0051]
[0052]
[0053] (2) Screening results of soluble microneedle composite matrix materials
[0054] Composite DMNs were prepared by combining brittle materials PVP K29-32, PVP K88-96, AP, and GEL with tough materials PVA and HPMC, respectively. The experimental results are shown in Table 5. Figure 3 .
[0055] Table 5. Comprehensive scoring table for DMNs prepared from composite matrix materials (W / W)
[0056]
[0057] According to Table 5 and Figure 3 It can be seen that the DMNs prepared by matrix solutions of PVP K29-32:PVA (1:1, W / W), PVPK88-96:PVA (1:1, W / W), PVP K88-96:PVA (2:1, W / W), PVP K88-96:HPMC (2:1, W / W), GEL:HPMC (1:1, W / W), and GEL:HPMC (1:2, W / W) all had high comprehensive scores of 60 points. Therefore, these 6 composite DMNs were selected for subsequent experiments.
[0058] 3. Optimization results of soluble microneedle preparation process
[0059] (1) Optimization results of centrifugal speed
[0060] The effect of centrifugation speed on DMNs is shown in Table 6. Figure 4 As shown.
[0061] Table 6. Results of the effect of centrifugal speed on DMNs
[0062]
[0063] From Table 6, Figure 5It can be seen that at a centrifugation speed of 1000 r / min, only a very small number of microneedles are formed. This may be because the centrifugation speed is too low, and the matrix solution cannot completely fill the mold, resulting in the inability to form needles. At a centrifugation speed of 2000 r / min, only a small number of needles fail to form, but the needle formation is poor. At a centrifugation speed of 3000 r / min, the matrix solution can fill the mold, the microneedle formation is good, the backing layer is intact, and it can be completely demolded. In conclusion, 3000 r / min is selected as the optimal centrifugation speed for preparing DMNs.
[0064] (2) Optimization results of centrifugation time
[0065] The effect of centrifugation time on DMNs is shown in Table 7. Figure 5 As shown.
[0066] Table 7. Results of the effect of centrifugation time on DMNs
[0067]
[0068] From Table 7, Figure 5 It can be seen that when the centrifugation time is 2 minutes, the matrix solution cannot completely fill the mold due to the short time, resulting in a large number of needles having concave surfaces, poor needle shape, and difficulty in demolding. When the centrifugation time is 6 minutes, the matrix solution can fill the mold, but a small number of needles still have concave surfaces and poor needle shape. When the centrifugation time is 10 minutes, the matrix solution can completely fill the mold, resulting in good needle shape, an intact backing layer, and no soluble microneedles or air bubbles. Therefore, 10 minutes is selected as the optimal centrifugation time for preparing DMNs.
[0069] (3) Results of Drying Temperature Optimization
[0070] The effect of drying temperature on DMNs is shown in Table 8. Figure 6 As shown.
[0071] Table 8. Results of the effect of drying temperature on DMNs
[0072]
[0073] From Table 8, Figure 6 It can be seen that when the drying temperature is 30℃, the needles cannot be completely dried due to the low temperature, resulting in easy bending during demolding and poor needle formability. When the drying temperature is 50℃, the microneedles can be completely dried and successfully demolded, with good needle formability. When the drying temperature is 70℃, the microneedle formability and demolding are no different from those at 50℃. Considering energy saving, 50℃ is selected as the optimal drying temperature for preparing DMNs.
[0074] (4) Results of Drying Time Optimization
[0075] The effect of drying time on DMNs is shown in Table 9. Figure 7 As shown.
[0076] Table 9. Results of the effect of drying time on DMNs
[0077]
[0078] From Table 9, Figure 7 It can be seen that when the drying time is 2 hours, the DMNs needles and backing layer cannot be completely dried, resulting in the microneedles being unable to be demolded normally. When the drying time is 4 hours, the microneedles can be completely demolded, but because the needles are not completely dried, they bend during demolding, resulting in poor needle shape. When the drying time is 6 hours, the microneedles are completely dried, can be completely demolded, have good needle shape, and the backing layer is intact and free of bubbles. Therefore, 6 hours is selected as the optimal drying time for preparing DMNs.
[0079] (5) Conclusion
[0080] The mechanical properties of DMNs prepared from six composite matrix materials—PVP K29-32:PVA (1:1, W / W), PVP K88-96:PVA (1:1, W / W), PVPK88-96:HPMC (2:1, W / W), GEL:HPMC (1:1, W / W), and GEL:HPMC (1:2, W / W)—were investigated. Compressive stress variation (CST) tests showed that all microneedles exhibited good puncture capability, effectively penetrating the skin without tip breakage. Furthermore, Parafilm… TM Membrane insertion experiments further confirmed that these microneedles can theoretically penetrate the stratum corneum and reach the dermal layer of the skin. Based on the above mechanical property evaluation, GEL:HPMC (1:2, W / W) was ultimately selected as the composite matrix material for preparing the microneedles. SEM images showed that the microneedles had smooth, conical surfaces, uniform thickness, and flat backing layers. The microneedles possessed sufficient mechanical strength to penetrate the skin and dissolved completely within 10 minutes after insertion. Using the microneedle morphology, backing flatness, and demolding performance as evaluation indicators, the optimal process parameters for preparing the composite matrix material DMNs were determined to be: centrifugation speed 3000 r / min, centrifugation time 10 min, drying temperature 50℃, and drying time 6 h.
[0081] 4. Analysis of Response Surface Experiment Results
[0082] (1) Results of the Box-Behnken experiment
[0083] The dosage of plasticizer, chemical agent, and penetration enhancer were selected as three influencing factors. Using TMP Q24 h(Y) as the response value, a star-point design-response surface methodology was employed to optimize the formulation. A total of 17 experiments were conducted, with three replicates for each group. The average value of Y was used for analysis. The experimental results are shown in Table 10.
[0084] Table 10 Box-Behnken Experimental Design and Response Values (n=3)
[0085]
[0086] (2) Model fitting and normal distribution results
[0087] Data were analyzed using Design-Expert 13 statistical software. Using TMP Q24 h as the response value, binomial regression equations were performed on the three factors: plasticizer dosage, dosage of chemical additives, and penetration enhancer dosage. The regression equations for Y are as follows:
[0088] Y=+2104.27-7.39A-12.98B+35.78C-35.32AB-14.32AC+60.22C-107.30A2-203.22B2
[0089] -251.50C2(R²=0.9702)
[0090] The correlation coefficient R² of the fitted equation indicates that the equation fits well and can predict experimental results with high accuracy. Analysis of the results using Design-Expert 13 statistical software reveals that the residuals follow a normal distribution with R². Figure 8 .Depend on Figure 8 It can be seen that the residual distribution tends to a straight line, indicating the cumulative permeation of TMP within 24 hours.
[0091] The normal distribution is uniform, the model fits well, and the error is small.
[0092] (3) Analysis of variance of Y
[0093] The significance test of the regression equation is shown in Table 11. The overall model of the regression equation is significant (P<0.05), while the lack-of-fit term is not significant (P>0.05). Therefore, the model is valid and can be used as a reference for optimizing the TMP transdermal patch formulation. Factor C has a significant effect on TMP Q24 h (P<0.05), and factors A², B², and C² have extremely significant effects on TMP Q24 h (P<0.01). Among the factors affecting TMP Q24 h, the order of influence from largest to smallest is: C (penetration enhancer dosage, %) > B (drug dosage, %) > A (plasticizer dosage, mL). Table 12 shows that the difference between the correlation coefficient R² and the corrected correlation coefficient R² is less than 0.2, indicating that the predicted value is close to the actual value and can accurately predict TMP Q24 h.
[0094] Table 11 Significance Test Table for Regression Equations
[0095]
[0096] Table 12 Analysis of Variance of Regression Equations
[0097]
[0098] (4) Effect surface analysis of Y
[0099] The results of the interaction between plasticizer (A), dosage (B), and penetration enhancer dosage (C) on the effect surface of Y are shown in the figure. Figure 9 , Figure 10 , Figure 11 A steeper slope on the response surface indicates a more significant interaction between the two factors, and a contour line closer to an ellipse also indicates a significant interaction. Figure 9 It can be seen that, with a fixed dosage of penetration enhancer, TMP Q24h first increases and then decreases with increasing dosage, and the slope of the curve is steeper than that of plasticizer dosage, indicating that the effect of dosage is greater than that of plasticizer dosage; from Figure 10 It can be seen that, with a fixed plasticizer dosage, TMP Q24 h first increases and then decreases with the increase of penetration enhancer dosage. The slope of the curve is steeper compared to the dosage, indicating that the effect of penetration enhancer dosage is greater than that of the dosage. Figure 11It can be seen that with a fixed dosage, TMP Q24 h first increases and then decreases with the increase of penetration enhancer dosage. Compared with plasticizer dosage, the surface slope is steeper, indicating that the effect of penetration enhancer dosage is greater than that of plasticizer dosage. According to the various 3D surface plots, the interaction between dosage and penetration enhancer dosage (BC) > the interaction between dosage and plasticizer dosage (AB) > the interaction between penetration enhancer dosage and plasticizer dosage (AC). Contour plots, as a visualization tool, can intuitively reflect the influence of each factor on the response value through the center position and shape of the graph. Among them, the center point of the graph usually represents the highest value of the response value, while the elliptical outline indicates that there is a significant interaction between two factors. By analyzing the three contour plots, we found that they all present an elliptical shape and have a clear center point, which further illustrates that the model's fitting effect is reliable.
[0100] (5) Results of Box-Behnken experiment on optimizing transdermal patch formulation
[0101] Using the cumulative penetration amount of TMP as the response value, the optimal formulation of the TMP transdermal patch was determined through a Box-Behnken experiment: 0.99 mL of plasticizer, 7.96% of the drug dosage, and 6.07% of the penetration enhancer. The regression model predicted the cumulative penetration amount of TMP for the optimal formulation to be 2105.77 μg / cm³. 2 As shown in Table 13, three TMP transdermal patches were prepared under the above conditions, and the Q24 h of TMP was calculated to be 2115.48 μg / cm. 2 The deviation from the theoretical prediction is within the allowable range.
[0102] Table 13 shows the theoretical and actual values (n=3).
[0103]
[0104] (5) Analysis of the results of the in vitro skin permeability test
[0105] Table 14. Transdermal patch penetration results using different penetration enhancement methods (n=3, x±SD)
[0106]
[0107] Depend on Figure 12As shown in Table 14, the ER value of the TMP transdermal patch group was only 1.72 times that of the TMP transdermal patch (without chemical penetration enhancer), the ER of the DMNs-TMP transdermal patch group (without chemical penetration enhancer) was 1.97 times that of the transdermal patch group (without chemical penetration enhancer), and the ER of the DMNs-TMP transdermal patch group was 2.71 times that of the TMP transdermal patch group (without chemical penetration enhancer). This indicates that the combined use of DMNs and chemical penetration enhancers greatly enhances the transdermal efficiency of TMP. The mechanism may lie in the dissolution of the microneedles after insertion into the skin, which forms micropores that facilitate the permeation of TMP, thereby significantly improving the transdermal performance of the drug.
[0108] (6) Conclusion
[0109] This chapter screened and optimized the formulation of TMP transdermal patches through single-factor experiments and response surface methodology. The determined formulation is as follows: polypropylene resin IV as the pressure-sensitive adhesive, 1.50 g; drug dosage of 7.96% of the patch formulation mass; triethyl citrate as the plasticizer, 0.99 mL; and isopropyl myristate as the chemical penetration enhancer, 6.07% of the patch formulation mass. This formulation is stable, simple, and reproducible. Due to the skin barrier function, relying solely on chemical penetration enhancers is insufficient to achieve more efficient transdermal TMP delivery. Therefore, this study considers the combined application of chemical and physical penetration enhancers to significantly improve the transdermal delivery efficiency of TMP. In in vitro skin permeability experiments, comparing TMP transdermal patches, DMNs-TMP transdermal patches, and blank TMP transdermal patches (without chemical permeation enhancers), the results showed that the cumulative permeation of TMP by DMNs-TMP transdermal patches increased significantly within 24 hours, with an ER 2.71 times that of the blank transdermal patch group, indicating that DMNs-TMP transdermal patches have a significant advantage in promoting transdermal TMP delivery.
[0110] 5. Pharmacokinetic Results in Vivo
[0111] (1) Pharmacokinetic behavior in rats
[0112] The results of the pharmacokinetic plasma concentration change curve experiment in rats are shown in the figure. Figure 13 .
[0113] Table 15 Pharmacokinetic Parameters (n=6, x±SD)
[0114]
[0115] After drug administration to rats, blood samples were collected at multiple predetermined time points, and the plasma TMP content was detected using a successfully established HPLC method. Based on the experimental data, the average plasma drug concentration-time curve was plotted (see...). Figure 13 ) and obtained the pharmacokinetic parameters (see Table 15). From Figure 13 As shown in Table 15, the elimination half-life of TMP in rats after intravenous injection was 1.940±0.036 h; after gavage administration, the elimination half-life was 3.928±0.331 h; after TMP transdermal patch administration, the elimination half-life was 6.204±0.495 h; while the elimination half-life of TMP in the DMNs-TMP transdermal patch group was significantly prolonged to 13.71±3.762 h. This indicates that TMP is eliminated relatively quickly in rats after intravenous injection and gavage administration, while the duration of action of TMP in rats is significantly prolonged in the two transdermal administration groups.
[0116] Regarding blood drug concentration, the TMP transdermal patch group reached peak blood drug concentration (Cmax = 0.38 ± 0.126 μg / mL) 6 hours after administration, followed by a slow decline. In contrast, the DMNs-TMP transdermal patch group reached peak blood drug concentration (Cmax = 1.069 ± 0.287 μg / mL) 4 hours after administration and maintained a relatively stable blood drug concentration with minimal fluctuations over the next 6 hours. Compared to the TMP transdermal patch group, the DMNs-TMP transdermal patch group not only shortened the time to peak blood drug concentration but also significantly increased the peak concentration.
[0117] Furthermore, the drug retention time in vivo in the DMNs-TMP transdermal patch group (MRT(0-t) = 15.451 ± 0.866 h) was significantly longer than that in the TMP transdermal patch group (MRT(0-48) = 11.707 ± 0.329 h), indicating that the DMNs-TMP transdermal patch group could significantly prolong the drug's duration of action in vivo. Simultaneously, the area under the curve (AUC(0-48) = 19.518 ± 5.466 h) in the DMNs-TMP transdermal patch group was also significantly greater than that in the TMP transdermal patch group (AUC(0-48) = 6.316 ± 2.721 h). This suggests that transdermal administration can maintain a relatively stable TMP concentration in rat plasma while avoiding the first-pass effect in the liver, thereby effectively increasing the blood drug concentration.
[0118] In conclusion, DMNs-TMP transdermal patches may have significant advantages in treatments requiring the maintenance of blood drug concentrations.
[0119] (2) Bioavailability
[0120] Bioavailability refers to the rate and extent to which an active ingredient, after being released from a drug formulation and absorbed by the body, can be utilized at the site of action. It is divided into two types: relative bioavailability and absolute bioavailability. Using the intravenous injection group and the oral gavage group as reference formulations, the absolute bioavailability (Fabs) and relative bioavailability (Frel) of TMP transdermal patches and DMNs-TMP transdermal patches were calculated according to formulas (A) and (B), and the results are shown in Table 6-8.
[0121] Formula A:
[0122] Formula B:
[0123] Where T represents the transdermal patch group or DMNs transdermal patch group, iv represents the intravenous injection group, R represents the gavage group, D represents the dosage, and AUC represents the area under the drug-time curve.
[0124] Table 16 Bioavailability Results
[0125]
[0126] The above description is merely a preferred embodiment of the present invention and should not be construed as limiting the scope of the invention. Any variations and improvements made to the present invention should be included within the scope of protection of the present invention.
Claims
1. A soluble microneedle, characterized in that, The raw materials for the soluble microneedles include gelatin and hydroxypropyl methylcellulose.
2. The soluble microneedles according to claim 1, characterized in that, The mass ratio of gelatin to hydroxypropyl methylcellulose is 1:
2.
3. A method for preparing soluble microneedles, characterized in that, The preparation method includes the following steps: (1) Preparation of matrix solution: Dissolve gelatin and hydroxypropyl methylcellulose in water at a mass ratio of 1:2 to prepare a matrix solution with a concentration of 15% w / w; (2) Filling the mold: Place the matrix solution in the mold and centrifuge at 3000 r / min for 10 min; (3) Drying and molding: The mold containing the matrix solution is dried at 50°C for 6 hours, and the soluble microneedles are obtained by demolding.
4. The preparation method according to claim 3, characterized in that, In step (1), the gelatin dissolves at 90°C and the hydroxypropyl methylcellulose dissolves at 50°C.
5. The use of the soluble microneedles according to any one of claims 1 to 3 in the preparation of transdermal drug delivery formulations.
6. A transdermal patch containing ligustrazine, characterized in that, The transdermal patch comprises: the soluble microneedles and drug layer as described in any one of claims 1 to 3; The drug layer contains the following components: Polyacrylic acid resin IV, triethyl citrate, isopropyl myristate, and tetramethylpyrazine.
7. The tetramethylpyrazine transdermal patch according to claim 6, characterized in that, The dosage of ligustrazine is 7.96% of the total mass of the transdermal patch layer; The amount of polypropylene resin IV used is 48.90% of the total mass of the transdermal patch layer; The amount of triethyl citrate used is 37.07% of the total mass of the transdermal patch layer; The amount of isopropyl myristate used is 6.07% of the total mass of the transdermal patch layer.